2001
DOI: 10.1007/s001920170030
|View full text |Cite
|
Sign up to set email alerts
|

Translabial Color Doppler Urodynamics

Abstract: Color Doppler ultrasound is a new method for documenting fluid leakage in the setting of videourodynamic testing. In order to compare color Doppler ultrasound with traditional fluoroscopic imaging we performed a prospective blinded comparative clinical study. Fifty-two consecutive patients undergoing urodynamic investigations for symptoms of incontinence or prolapse were examined using fluoroscopy and translabial color Doppler ultrasound to document stress leakage. The investigators were blinded to each other'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Benson also described urethrovesical junction hypermobility in patients with stress urinary incontinence on perineal ultrasound [9] and more recently, others have found that retrovesical angle rotation and bladder neck descent at Valsalva on ultrasound are strongly associated with genuine stress incontinence [10,11]. When analysis focuses on ultrasound visualization of bladder leakage rather than simple assessment of mobility patterns, sensitivity in diagnosing SUI is much higher [12]. This technique, however, uses ultrasound to establish if leakage occurs, an issue independent of whether urethral mobility is associated with ultrasound diagnosis of SUI.…”
Section: Discussionmentioning
confidence: 99%
“…Benson also described urethrovesical junction hypermobility in patients with stress urinary incontinence on perineal ultrasound [9] and more recently, others have found that retrovesical angle rotation and bladder neck descent at Valsalva on ultrasound are strongly associated with genuine stress incontinence [10,11]. When analysis focuses on ultrasound visualization of bladder leakage rather than simple assessment of mobility patterns, sensitivity in diagnosing SUI is much higher [12]. This technique, however, uses ultrasound to establish if leakage occurs, an issue independent of whether urethral mobility is associated with ultrasound diagnosis of SUI.…”
Section: Discussionmentioning
confidence: 99%
“…Two papers investigated the use of translabial colour Doppler ultrasound. 139,141 This was compared as an alternative to fluoroscopy for the detection of urinary leakage during urodynamic investigation for the diagnosis of USI, DO and mixed incontinence.…”
Section: Urodynamics Compared With Ultrasoundmentioning
confidence: 99%
“…VLPP and CLPP were assessed during perineal ultrasound examination. Urine leakage was identified with color Doppler velocimetry (CDV) [14,15]. Sensitivity of the CDV was increased using an ultrasound contrast medium (Levovist) [16] (Fig.…”
Section: Methodsmentioning
confidence: 99%